THE SYMBOLIC ROLE OF THE COLOURS “GOLD” AND “SILVER” IN ENGLISH PROVERBS - Sherdjanova Sevara Qahramanovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
Proverbs serve as a vital component of language and culture, encapsulating collective wisdom, societal norms, and values in succinct and memorable expressions. Among the symbolic elements in proverbs, colors hold a unique place, often conveying profound meanings. This study focuses on the symbolic role of the colors “gold” and “silver” in English proverbs, analyzing their cultural significance and the messages they embody.